N-(Diphenylcarbamothioyl)-3-methylbenzamide - Hakan Arslan; Nevzat Külcü; Ulrich Flörke; Gün Binzet (Acta Crystallographica Section E, 2009)
The synthesis of the title compound, C21H18N2OS, involves the reaction of 3-methylbenzoyl chloride with potassium thiocyanate in dry acetone followed by condensation of the 3-methylbenzoyl isothiocyanate with diphenylamine. The carbonyl [C—O = 1.215 (2) Å] and thiocarbonyl [C—S = 1.6721 (17) Å] distances indicate that these correspond to double bonds. The short C—N bonds at the center of the molecule reveal the effects of resonance in this part of the molecule. The conformation of the molecule with respect to the thiocarbonyl and carbonyl groups is twisted. The 3-methylphenyl and two phenyl rings are also twisted, with dihedral angles of 75.67 (9) and 14.91 (9)°. The phenyl rings are rotated out of the mean plane of the N—C—S—N atoms by 66.87 (8) and 78.40 (9)°. Pairs of molecules are linked into centrosymmetric dimers via intermolecular N—H...S interactions and a C—H...O link also occurs. The dimers are stacked along the a axis.